2009
DOI: 10.1007/s11244-008-9146-4
|View full text |Cite
|
Sign up to set email alerts
|

Zeolites in Microsystems for Chemical Synthesis and Energy Generation

Abstract: Zeolites were incorporated as membrane and catalyst in chemical microsystems for portable energy generation and fine chemical synthesis. Microfabricated HZSM-5 micromembrane was used as a proton-exchange membrane in a miniature direct methanol fuel cell (l-DMFC). The good proton conductivity of HZSM-5 micromembrane was attributed to a Grotthus-like diffusion of protons along the water molecules bridging neighboring aluminum sites in the hydrated HZSM-5. The 6-lm thick HZSM-5 micromembrane exhibited comparable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 66 publications
0
14
0
Order By: Relevance
“…Miniaturization is shown to benefit membrane processes and their use has been demonstrated for various reactions including selective oxidations [68][69][70], direct hydroxylation [71,72] and Knoevenagel condensation reactions [73][74][75][76]. Membrane research in fuel cell mainly concerns hydrogen separation [77][78][79][80][81][82] and proton-exchange membranes [40,41]. This work demonstrates that zeolites are promising materials for proton-exchange membranes, but further improvements in membrane transport by selecting large pore zeolite of higher aluminum contents (e.g., faujasite, zeolite Beta) and by decreasing the diffusion pathways through the zeolite (e.g., thinner membrane and b-oriented HZSM-5 are needed to yield a higher fuel cell performance.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Miniaturization is shown to benefit membrane processes and their use has been demonstrated for various reactions including selective oxidations [68][69][70], direct hydroxylation [71,72] and Knoevenagel condensation reactions [73][74][75][76]. Membrane research in fuel cell mainly concerns hydrogen separation [77][78][79][80][81][82] and proton-exchange membranes [40,41]. This work demonstrates that zeolites are promising materials for proton-exchange membranes, but further improvements in membrane transport by selecting large pore zeolite of higher aluminum contents (e.g., faujasite, zeolite Beta) and by decreasing the diffusion pathways through the zeolite (e.g., thinner membrane and b-oriented HZSM-5 are needed to yield a higher fuel cell performance.…”
Section: Discussionmentioning
confidence: 99%
“…1b). The ZSM-5 film was grown by hydrothermal regrowth at 423 K for 48 h from a synthesis solution containing 40 SiO 2 :2 Al 2 O 3 :0.5 TPA 2 O:5 Na 2 O:20,000 H 2 O [37][38][39][40][41]. The self-supporting micromembranes were obtained after etching away the remaining 50 lm Si layer and removing the TPA ?…”
Section: Preparation Of Supported and Self-supportingmentioning
confidence: 99%
See 1 more Smart Citation
“…Although most zeolites have lower proton conductivity than the commercial PFSA, they have considerably better mechanical strength and could be fabricated into ultrathin membranes. Recent works by the group of Yeung investigated HZSM-5 as proton conducting membrane for microfabricated miniature hydrogen PEMFCs [75] and DMFCs [76]. They chose HZSM-5 as an experiments model, and calculations indicated that the proton mobility in ZSM-5 was among the highest in zeolites [33,38,77].…”
Section: Zeolite and Mesoporous Inorganic Membranesmentioning
confidence: 99%
“…The mentioned areas substantially contributed to a much deeper insight into the zeolite chemistry. Recently, also novel applications of zeolites like gas storage microsystems for chemical synthesis and energy generations were discussed [18,19].…”
Section: Introductionmentioning
confidence: 99%